2010
DOI: 10.1063/1.3524230
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Co/Pt and Co/Pd superlattice films for MgO-based perpendicular magnetic tunnel junctions

Abstract: Ultrathin [Co/Pt]n and [Co/Pd]n superlattice films consisting of 0.14–0.20-nm-thick Co and Pt(Pd) layers were deposited by sputtering. A large perpendicular magnetic anisotropy [(3–9)×106 ergs/cm3] and an ideal square out-of-plane hysteresis loop were attained even for ultrathin superlattice films with a total thickness of 1.2–2.4 nm. The films were stable against annealing up to 370 °C. MgO-based perpendicular magnetic tunnel junctions with this superlattice layer as the free layer showed a relatively high ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
149
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(158 citation statements)
references
References 22 publications
6
149
1
2
Order By: Relevance
“…Thus, since it is widely believed that the Co/Pd intermixing or Pd diffusion is one of the main factors for PMA degradation during annealing process, 16 Co and Pd thicknesses were frequently used in the MLs. 4,14,16 Therefore, more detailed studies are necessary to clarify the structural characteristics in ML configurations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, since it is widely believed that the Co/Pd intermixing or Pd diffusion is one of the main factors for PMA degradation during annealing process, 16 Co and Pd thicknesses were frequently used in the MLs. 4,14,16 Therefore, more detailed studies are necessary to clarify the structural characteristics in ML configurations.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] Among them, artificial ML matrices composed of ferromagnetic and noble metals, such as Co/Pd, Co/Pt, Fe/Pd, and Fe/Pt, have shown that ML matrices are promising candidates for use in p-MTJs. 4,[9][10][11][12] Alternating two ultra-thin layers with different thicknesses in the ML matrix permits appreciable tuning of magnetic characteristics and yields strong PMA features. These PMA properties may originate from possible interface spin-orbit coupling between ferromagnetic/noble metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we would like to evaluate the SOT in the Co/Pt multilayers (MLs), which possesses good enough PMA with tunable volume of the FM layer and also shows a good magnetoresistance in MgO-based 3 magnetic tunnel junctions with the interfacial CoFeB insertion. 14,15 Although a high SOT has been reported on the Co/Pd MLs recently, 13 no systematic works have been done for explaining the presence of SOT in the multilayers, where the spin currents from heavy metal may counteract each other and no Rashba interaction can be seen without structure inversion asymmetry. By conducting the lock-in technique, [16][17][18] the dependence of SOT efficiencies of the Co/Pt MLs on different repeating layer number (N) is investigated.…”
mentioning
confidence: 99%
“…Pd) elements, [3][4][5][6][7][8][9] which exhibit large PMA that promisingly overcomes the shape in-plane magnetic anisotropy and thermal fluctuations on a device level.…”
mentioning
confidence: 99%